Q. 384.0( 2 Votes )

If tan2</sup

Answer :

Formula: -


(i) tan2x = sec2x – 1


(ii) cos2x = 1 – sin2x


Taking L.H.S and applying formula (i) we get,


tan2A – tan2B = sec2A – 1 – (sec2B – 1)


tan2A – tan2B = sec2A – 1 – sec2B + 1


tan2A – tan2B = sec2A – sec2B





Applying formula (ii) we get,




L.H.S = R.H.S


Hence, Proved.


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses